Participatory Project Implementation and Sustainability of Government Funded Projects a Case study of Parish Development Model in Kabale District, Uganda - Moses, Agaba; Turyasingura, John Bosco (International Journal of Current Science Research and Review, 2023)
A case study of Parish Development Model in Kabale District was used in the study to explore the impact of participatory project implementation on the sustainability of government-funded projects in Uganda. Sustainability of government funded project was a dependent variable while participatory project implementation was independent variable. A cross-sectional survey was conducted before the research began. We gathered information from 75 respondents, and combined quantitative and qualitative analysis. Descriptive, bivariate, and multivariate methodologies were all used in the analysis, which was carried out on three different levels. Frequency tables were utilized to display the data because the descriptive analysis called for the presentation of just one variable and its characteristics. The bivariate correlations between the dependent variable and the predictor components were examined using a Pearson correlation matrix. The dependent variable was regressed against the revised predictor factors at the multivariate level (sustainability of government project). An analysis of the data was done using a linear regression model. According to the findings of a regression study, participatory project implementation has a favorable impact on the effectiveness of parish development models in Kabale District (coef = -0.890, p-value = 0.000). The fundamental conclusion of this study is that the success of a parish development model project is significantly influenced by the implementation of participatory projects. The study suggests that in order to ensure the sustainability of the parish development model, more emphasis should be placed on adopting participatory project implementation through defining the project implementation team, customer satisfaction, project outputs realization, and project expansion and scale-up.